Single-Channel Kinetic Analysis for Activation and Desensitization of Homomeric 5-HT3A Receptors - Corradi, Jeremias (2009)
The 5-HT3A receptor is a member of the Cys-loop family of ligand-gated ion channels. Due to its low conductance, kinetic analysis of this receptor has been restricted to the macroscopic level. We introduced mutations in the 5- HT3A subunit to obtain a high-conductance form so that single-channel currents can be detected. At all 5-HT concentrations (>0.1 mM) channel activity appears as opening events in quick succession forming bursts, which, in turn, coalesce into clusters. By combining single-channel and macroscopic data we generated a detailed kinetic model that perfectly describes activation, deactivation and de- sensitization. The model shows that full activation arises from receptors with three molecules of agonist bound. It also reveals an earlier conformational change of the fully-liganded receptor (flipping) that occurs while the channel is still closed. From this pre-open state the receptor enters into an open-closed cycle involving three open states, which conforms the cluster whose duration parallels the time constant of desensitization. This suggests that at a synapse the lifetime of the elementary response of 5-HT3A receptors is determined mainly by desensitization. Since the desensitized state is a stable state, the in- ter-response latency is expected to be prolonged. The present kinetic model provides a foundation for studying molecular mechanisms of drug action. We show that mutations at valine 100 of M4 affect opening and closing rates within the open-closed cycle. This reveals that the outermost transmembrane domain is important for appropriate gating and shows a high conservation of M4 function among members of this superfamily.